Effects of dietary imbalances of micro- and macronutrients on the ocular microbiome and its implications in dry eye disease - Madeline Pilkington; Declan Lloyd; Brad Guo; Stephanie L. Watson; Kenneth Gek-Jin Ooi (Open Exploration Publishing Inc., 2024)
Dry eye disease (DED) is a complex and multifactorial ocular surface disease affecting a large proportion of the population. There is emerging evidence of the impact of the microbiomes of the ocular surface and gut on the symptoms of DED, with many parallels being drawn to inflammatory diseases of other organ systems. A key factor involved in the promotion of healthy microbiomes, and which has been associated with ocular surface disease, is micro- and macronutrient deficiency. A comprehensive review of how these deficiencies can contribute to DED is absent from the literature. This review reports the composition of healthy ocular and gut microbiomes, and how nutrient deficiencies may impact these floral populations, with linkage to the subsequent impact on ocular health. The review highlights that vitamin B1 and iron are linked to reduced levels of butyrate, a fatty acid implicated in inflammatory conditions such as ulcerative colitis which itself is a condition known to be associated with ocular surface diseases. Vitamin B12 has been shown to have a role in maintaining gut microbial eubiosis and has been linked to the severity of dry eye symptoms. Similar beneficial effects of gut microbial eubiosis were noted with vitamin A and omega-3 polyunsaturated fatty acids. Selenium and calcium have complex interactions with the gut microbiome and have both been implicated in the development of thyroid orbitopathy. Further, diabetes mellitus is associated with ocular surface diseases and changes in the ocular microbiome. A better understanding of how changes in both the gut and eye microbiome impact DED could allow for an improved understanding of DED pathophysiology and the development of new, effective treatment strategies.